PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN Usaha Dagang - Rizky Oktavian, Ade (Manageable, 2022)
This research was motivated by the low performance of employees of the Trading Business in Central Java. The problem in this study is the dominant variables in influencing the performance of Trading Business employees including transformational leadership style, organizational culture and motivation". The purpose of this study is to analyze the influence of each variable, transformational leadership style (X1), organizational culture (X2), motivation (X3) on employee performance (Y).In this study, data were collected through a questionnaire method on 80 people from a total of 80 employee populations. UD. in Central Java is spread in several other districts such as Banjarnegara, Purwokerto, Wonosobo and several other districts.The results of the study from 80 respondents who were processed using classical assumptions assisted by the SPSS version 22 program showed the results that transformational leadership style, organizational culture and motivation influenced the performance of employees of the Central Java Trading Business. All data meet the requirements of classical assumptions consisting of normality, homogeneity, and equality of regeresi lines.